1998
DOI: 10.1142/s0217751x98001736
|View full text |Cite
|
Sign up to set email alerts
|

Faddeev-Jackiw Approach to Gauge Theories and Ineffective Constraints

Abstract: The general conditions for the applicability of the Faddeev-Jackiw approach to gauge theories are studied. When the constraints are effective a new proof in the Lagrangian framework of the equivalence between this method and the Dirac approach is given. We find, however, that the two methods may give different descriptions for the reduced phase space when ineffective constraints are present. In some cases the Faddeev-Jackiw approach may lose some constraints or some equations of motion. We believe that this in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…We denote this transformation by 10) where D µ is the Yang-Mills covariant derivative (in its action on spacetime scalars and Yang-Mills vectors). Under this transformation, the field transforms as…”
Section: A Yang-mills Gauge Transformationsmentioning
confidence: 99%
“…We denote this transformation by 10) where D µ is the Yang-Mills covariant derivative (in its action on spacetime scalars and Yang-Mills vectors). Under this transformation, the field transforms as…”
Section: A Yang-mills Gauge Transformationsmentioning
confidence: 99%
“…This method, when rephrased, as we do here, in terms of the canonical Lagrangian, is just a reduction procedure from L c to L that can be independently justified. 18 We prove in the appendix that it is legitimate to substitute within the Lagrangian (L c in our case) the auxiliary variables, that is, the variables (p and λ in our case) that can be isolated by using their own equations of motion. Now, given a generalized Noether transformation δ c q i associated, according to (61), with a constant of motion G c , we can readily prove that δq i := (δ c q i )| (p=p,λ=v) (λ = v includes, obviously,λ =v = (∂v/∂q)q +q(∂v/∂q), and so on forλ, etc.)…”
Section: Back To the Original Lagrangianmentioning
confidence: 92%
“…In the Refs. [10,11] irregular systems of the type II were discussed. It was pointed out that there was a possible loss of dynamical information in some cases.…”
Section: Nonlinear Constraintsmentioning
confidence: 99%
“…In Refs. [10,11] it was observed that Dirac's conjecture may not hold in the presence of irregular constraints of type II.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation